Duration on ART, Alcohol Use and HIV Stage May Predict Risky Sexual Behavior in a Resource-limited Environment: A Cross-sectional Study - New-Aaron, Moses; Kingi, Happiness; Meza, Jane L.; Goedert, Martha H.; Kibusi, Stephen M; Mkhoi, Mkhoi L.; Mayengo, Caroline D.; Charles, James; Shabani, Siraji; New-Aaron, Temitope O.; Sumba, Samwel; Cheney, Anlan (Current HIV Research, 2021)
Background: The intention of antiretroviral therapy (ART) and regular clinic visits are to engender safe sex attitudes among HIV-infected individuals. However, this may not be the case due to the perceived therapeutic benefits of ART and may result in exposure to drug-resistant HIV strains. Objectives: We aimed to determine the prevalence and predict the factors associated with risky sexual behaviors among ART users in a resource-limited environment. Methods: Two hundred and ninety-one sexually active ART-users aged 18-50 years and seeking care at the HIV clinic in Dodoma, Tanzania, participated in this study. The outcome variables modeled in a logistic regression were condom use, multiple sex partners, casual sex partners, and payment for sex. The predictors included in the models were the patients' socio-demographic characteristics. In addition, a new variable, sexual risk scores, was generated by culminating all the outcome variables. Finally, a multiple Poisson regression with the socio-demographic variables of the participants was used to model the sexual risk scores. Results: Patients reported inconsistent/no condom use (44%), payment for sex (4%), casual sex encounters (13%), multiple sex partners (21%), and STD symptoms (15%). While having a casual sexual partner was significantly associated with age group in a Pearson Chi-square (p=0.0147), participants ≤35 years old were less likely to have single-sex partners than older participants (AOR: 0.188, 95 C.I: 0.042-0.849). Meanwhile, the likelihood of condom use was higher among participants with no HIV-infected family members (AOR= 2.409, 95% C.I:1.236,4.697) and among participants who had single-sex partners (AOR= 2.721, 95% C.I.: 1.115,6.640); these participants were less likely to report STD symptoms (AOR=0.265, 95% C.I.: 0.081-0.865). Adjusted analysis showed that estimated mean sexual risk scores significantly increased (mean, λ=1.61, 95% C.I:1.0817-2.4063) for recent ART recipients (within 1-3 years vs. ≥8 years). However, sexual risk scores of participants with HIV stage 3 were 38.8% lower than participants at stage 4 (95% C.I.: 0.3910-0.9558), and non-alcohol drinkers had an adjusted mean sexual risk score of 29% lower than participants who were alcohol drinkers (95% C.I.: 0.5102-0.9879). Conclusion: Researchers should prioritize patients at HIV CTC for education concerning safe sexual practices for those characterized by alcohol consumption, younger age (less than 35 years old), HIV stage 4, or commencement of ART within three years.
Keywords: HIV stage